Descending Necrotizing Mediastinitis: A Potential Consequence of Odontogenic Infection. (2nd March 2022) - Walshaw, Emma G; Taylor, Richard; Parmar, Jiten
Abstract : Descending necrotizing mediastinitis is a potential consequence of cervicofacial infection, which can promptly progress into a life-threatening disease, with the sequelae of severe sepsis, organ failure and death. This article highlights the importance of this pathology and discusses key signs and symptoms that may be identified when performing an assessment on a patient with a large cervicofacial swelling. This article also describes the case of a young and healthy patient who experienced this pathology from an odontogenic source. CPD/Clinical Relevance: Descending necrotizing mediastinitis, although rare, is a potentially life threatening consequence of odontogenic infection and awareness of it is imperative for dental professionals.